Improving personal protective equipment awareness among rural farmers in Indonesia: An evaluation of community-based education in Kampung Beru Hamlet - Asir, Muhammad Faiz Fawwaz; Rakhman, Alfina Sari; Wijaya, Dian Rezki`; Mallapiang, Fatmawaty (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2025)
Despite growing concerns over occupational health, the improper use of personal protective equipment (PPE) among pesticide-exposed farmers remains a critical challenge, particularly in rural areas. Previous interventions often lacked sustained impact and contextual engagement. This study aimed to evaluate the effectiveness of an educational program designed to improve PPE awareness and use among farmers in Dusun Kampung Beru, Indonesia. Using a quantitative approach with the Asset-Based Community Development (ABCD) method, eleven local farmers participated in a structured intervention involving a pre-test, a post-test I during the second community-based learning session (PBL II), and a post-test II during PBL III conducted six months later. The findings revealed a significant increase in farmers’ knowledge, with the median score improving from 90 (pre-test) to 100 (post-test I), maintaining the same level in post-test II. The proportion of participants categorized as having adequate knowledge rose from 27.3% to 63.6% and further to 80% over the evaluation period. However, challenges in PPE usage persisted due to discomfort and equipment quality. The study highlights that while community-based educational programs can effectively enhance awareness, their long-term success depends on continued support, including the provision of comfortable PPE, local leadership involvement, and culturally sensitive strategies. This intervention model has implications for public health efforts in similar rural settings.